Augmented Reality and AI in Remote Geospatial Analysis: Enhancing Decision-Making in Crisis Management (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In an era of increasing environmental and geopolitical challenges, the integration of Augmented Reality (AR) and Artificial Intelligence (AI) in remote geospatial analysis is transforming crisis management and decision-making. By combining AI-driven data analytics with immersive AR visualization, emergency responders, policymakers, and geospatial analysts can gain real-time, interactive, and highly accurate insights into crisis situations. This fusion enhances the interpretation of satellite imagery, LiDAR data, and drone surveillance, allowing for faster, more precise, and proactive responses to natural disasters, humanitarian crises, and security threats.AI-powered predictive modeling and machine learning algorithms enable the early detection of potential hazards, optimizing resource allocation and mitigating risks before crises escalate. Meanwhile, AR facilitates intuitive, hands-on engagement with geospatial data, transforming complex datasets into interactive 3D models that improve situational awareness and operational efficiency. These advancements significantly reduce response times, enhance coordination among agencies, and improve disaster resilience in high-risk environments.This paper explores the technological convergence of AR and AI in geospatial analysis, highlighting key applications, case studies, and future directions in crisis management. It discusses the benefits, challenges, and ethical considerations of integrating these technologies, emphasizing their potential to redefine decision-making processes in disaster preparedness, emergency response, and risk assessment. By leveraging AI-driven analytics and AR-enhanced visualization, organizations can build more resilient, adaptive, and efficient crisis management frameworks for a rapidly changing world.